Economic precariousness: A new channel in the housing market cycle - Philip Arestis; Ana Rosa Gonzales-Martinez (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
Demographic and institutional elements as important drivers of the housing market should not be neglected since it is not only financial and monetary elements that matter in the case of the housing market. In this context, one relationship, which still remains unclear, is the relationship between the housing and the labour markets. Some research has been under-taken to support the hypothesis that high rates of homeownership lead to high unemploy-ment via increases in the reservation wage. However, further research is needed to address the possible implications of the institutional settings of the labour market in the dynamics of the housing market. The aim of this paper is to bring some light on the link between both markets. In particular, this contribution explains how the housing cycle could be ?amplified? via a new channel, i.e. economic precariousness, which is closely related to job insecurity. Subsequently, we provide evidence in the case of five developed economies, Ireland, the Netherlands, Spain, the United Kingdom and the United States, over the period 1985-2013.
Keywords: C22; R31; 330; Economic precariousness; Job insecurity; Labour markets; House prices; Cointegration techniques